Production of acylglycerol esters - Lai, Oi Ming; Yusof, Mohd. Suria Affandi; Lo, Seong Koon; Long, Kamariah; Tan, Chin Ping; Taharuddin, Shawaluddin; Hashim, Khairudin (2010)

(untitled)
The present invention relates to the production of oil and fat containing acylglycerol esters including diacylglycerols, medium-chain and long-chain fatty acid triacyglycerols comprising esterification reaction between an acyl group donor and an acyl group acceptor in the presence of a heterogeneous chemical catalyst consisting of an ion-exchange resin preparation to obtain a reaction fluid that is further subjected to dehydration and at least one separation method, thus producing diacylglycerols and/or medium-chain and long-chain fatty acid triacyglycerols at a high yield in a short period of time.